Determining the Teacher Education Needs for the Treatment of the Problem Behaviors of Students with Autism Spectrum Disorder - Kocak, Fatih; Sari, Hakan (Asian Journal of Education and Training, 2021)
This study was carried out to test the effect of the training program developed for teachers who are involved in the education of students with ASD to enable them to provide quality education in the education and training process. To determine the teacher training needs for the treatment of problem behaviors that occur in students with Autism Spectrum Disorder (ASD) is the aim of this study. For this purpose, inter-views under four sub-headings were conducted. These titles are the determination of behavior, programming, program implementation, and Program Evaluation. In the research, a qualitative case study design was preferred. The data were obtained from 22 teachers working with ASD students through face-to-face interviews, audio and video recordings using semi-structured interview forms. The analysis of the data was done through the descriptive analysis technique. As a result of the research, most of the teachers stated that they did not find themselves sufficient regarding the problem behaviors and treatment of students with ASD. The in-depth results of the study were discussed in line with the teacher needs, relevant qualitative research, and implications for future research and applications were suggested.